RELATIONSHIP INTEREST IN LEARNING AND INTELLIGENCE INTELLECTUAL WITH LEARNING RESULTS ISLAMIC EDUCATION OF STUDENTS STATE ELEMENTARY SCHOOL IN BANDAR SETIA VILLAGE DISTRICT PERCUT SEI TUAN - Nuralam Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine the magnitude of the relationship of interestin learning and intellectual intelligence to the learning outcomes of IslamicEducation in elementary school students in Bandar Setia Village, PercutSei Tuan District. The sample in this study amounted to 34 people takenfrom 10% of the total student population of 333 people. This study usesdata collection tools in the form of questionnaires. The questionnaire iscompiled based on variable indicators and then conducted a trial to therespondents who entered the sample in this study. The data analysisprocess was carried out in three stages: (1) describing the data of theresearch variables, (2) testing the analytical requirements, (3) testing thehypothesis to determine the relationship between the variables of thestudy using correlation analysis techniques. Conclusions based on dataanalysis and testing process are described as follows: (1) learning interesthas a positive and significant relationship with learning outcomes. (2).intellectual intelligence has a positive and significant relationship withlearning outcomes. and (3). learning interest and intellectual intelligencetogether have a positive and significant relationship. On the basis of theresults of these studies it can be stated that the interest in learning andintellectual intelligence has a positive and significant effect on learningoutcomes both individually and together.